2022
DOI: 10.7759/cureus.22249
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Simulation-Based Point-of-Care Ultrasound Education: A Systematic Review of MedEdPORTAL Curricula

Abstract: Point-of-care ultrasonography (POCUS) is increasingly recognized as a safe, efficacious, and cost-effective diagnostic and procedural tool used by many medical disciplines. Although standardized POCUS curricula are lacking, simulation represents an effective modality to teach the fundamentals of POCUS in medical education. We sought to characterize POCUS simulation cases available within MedEdPORTAL, the primary repository of learning resources for health professions, to highlight areas for future curricular d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 23 publications
0
11
0
3
Order By: Relevance
“…Thus, considering the pandemic scenario experienced two years ago, it was necessary to develop a teaching system in ultrasonography in the environment where patient care is provided. Point-of-care ultrasonography has become a ubiquitous diagnostic tool, and there has been a growing A systematic review published this year concluded that although simulation provides a highly promising solution to the need for increased point-of-care ultrasound instruction, the widespread use of this simulation for this purpose may be limited by the financial costs of high-fidelity training equipment 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, considering the pandemic scenario experienced two years ago, it was necessary to develop a teaching system in ultrasonography in the environment where patient care is provided. Point-of-care ultrasonography has become a ubiquitous diagnostic tool, and there has been a growing A systematic review published this year concluded that although simulation provides a highly promising solution to the need for increased point-of-care ultrasound instruction, the widespread use of this simulation for this purpose may be limited by the financial costs of high-fidelity training equipment 23 .…”
Section: Discussionmentioning
confidence: 99%
“…However, further research is needed in this field as there is more room for developing more advanced POCUS simulations and incorporating them into undergraduate and graduate medical curricula. 31 In another study involving internal medicine residents in their PGY-1 years, after 30-h POCUS training, there was a statistical increase in knowledge regarding image acquisition and interpretation and using the results for clinical decision making. 32 …”
Section: Reviewmentioning
confidence: 99%
“…Simulationsbasiertes Training hat sich in einigen Ländern bereits als festes Trainingsmodul für die Ausbildung in der fokussierten, klinischen Sonographie (POCUSpoint of care ultrasound) durchgesetzt, wie beispielsweise in der Schweiz [98] oder den USA [49,101]. In einer kritischen amerikanischen Analyse fiel jedoch auf, dass bei teils hohen Gerätekosten zwar eine hohe Anwenderzufriedenheit zu verzeichnen war, jedoch in 7 von 8 der identifizierten Curricula keine objektive Lernerfolgskontrolle erfolgte [101]. Darüber hinaus ist in der Anästhesie das simulationsgestützte Training für den perioperativen Ultraschall Bestandteil einiger US-amerikanischer Curricula [88] sowie in Korea beispielsweise für die ultraschallgesteuerte Regionalanästhesie mittels Phantomtraining fest etabliert [68].…”
Section: Kompetenzunclassified
“…Simulationsbasiertes Training hat sich in einigen Ländern bereits als festes Trainingsmodul für die Ausbildung in der fokussierten, klinischen Sonographie (POCUSpoint of care ultrasound) durchgesetzt, wie beispielsweise in der Schweiz [98] oder den USA [49,101]. In einer kritischen amerikanischen Analyse fiel jedoch auf, dass bei teils hohen Gerätekosten zwar eine hohe Anwenderzufriedenheit zu verzeichnen war, jedoch in 7 von 8 der identifizierten Curricula keine objektive Lernerfolgskontrolle erfolgte [101].…”
Section: Kompetenzunclassified